Step by step: A microgenetic study of the development of strategy choice in infancy. (16th December 2014) - Berger, Sarah E.; Chin, Brian; Basra, Sandeep; Kim, Hannah
<x xml:space="preserve">Abstract</x> To examine patterns of strategy choice and discovery during problem‐solving of a novel locomotor task, 13.5‐ and 18‐month‐old infants were placed at the top of a staircase and encouraged to descend. Spontaneous stair descent strategy choices were documented step by step and trial by trial to provide a microgenetic account of problem‐solving in action. Younger infants tended to begin each trial walking, were more likely to choose walking with each successive step, and were more likely to lose their balance and have to be rescued by an experimenter. Conversely, older infants tended to begin each trial scooting, were more likely to choose scooting with each successive step, and were more likely to use a handrail to augment balance on stairs. Documenting problem‐solving microgenetically across age groups revealed striking similarities between younger infants' strategy development and older children's behaviour on more traditionally cognitive tasks, including using alternative strategies, mapping prior experiences with strategies to a novel task, and strengthening new strategies. As cognitive resources are taxed during a challenging task, resources available for weighing alternatives or inhibiting a well‐used strategy are reduced. With increased motor experience, infants can more easily consider alternative strategies and maintain those solutions over the course of the trial.